Report of the Committee on the Elimination of Discrimination against Women, Sixty-fifth Session - United Nations Department for General Assembly; Conference Management (United Nations, 2010)
Official records of the Report of the Committee on the Elimination of Discrimination against Women: Forty-Fourth Session (20 July-7 August 2009) Forty-Fifth Session (18 January-5 February 2010).